Academic Quality In Municipal Training Programs: A Systematic Review Of The Last 5 Years (Architecture Image Studies, 2025)
This systematic review follows the strict PRISMA 2020 protocol with its 27 check items, examining the academic quality of municipal training programs between 2021 and 2025. It focuses on Latin American countries such as Ecuador and Colombia. The research question addresses the factors affecting planning, work, and evaluation indicators, as well as problems in different locations, including inadequate facilities, limited access to digital technology, resource scarcity in affected rural areas, and high dropout rates, which have increased due to the gaps created by the pandemic. Of the initial number of records found in databases such as Scopus, Web of Science, SciELO, Dialnet, and ALICIA Concytec, only 11 studies were included in this work. The findings show the importance of forging alliances between different sectors, sustainably monitoring the work, and conducting periodic evaluations to improve pedagogical knowledge in order to reduce social and economic disparities, so that everyone has the same opportunities in the territory. It is concluded that municipal policies should prioritize curricular alignment with labor demands, digital inclusion, and community participation in decisions made by the local government regarding training. The weaknesses include methodological heterogeneity and publication biases; therefore, meta-analyses are recommended in the future, along with an openness to gray literature for robust generalizations.